Pengaruh Penambahan Minyak Zaitun Terhadap Karakteristik dan Reologi Edible Film Berbahan Dasar Gluten: The Effect of Addition of Olive Oil on The Properties and Rheology of Gluten-Based Edible Films - Nancy Siti Djenar; Joko Suryadi; Nisa Siti Nursaadah; Erina Putri (KOVALEN: Jurnal Riset Kimia, 2022)
Gluten vegetable protein can be used as an alternative source of biopolymer as the basic material for edible film other than polysaccharides. Gluten-based edible films have a poor water vapor barrier and high cohesive and viscoelastic properties, therefore the addition of lipids and plasticizers is required. In this study, olive oil was added to reduce its permeability to water vapor, while glycerin was added to produce a more flexible edible film. The results showed that the addition of 1% olive oil could reduce the lowest water vapor transmission rate of 9.14 g/m2/24 hours with a thickness of 0.248 mm, tensile strength of 16.64 mPa, and elongation of 419.5%. The four characteristics are in accordance with the Japanese Industrial Standard. The antimicrobial testing on edible films showed that the addition of 0-2% olive oil could inhibit the growth of E. coli, while A. niger and R. oryzae 0-2% olive oil could not inhibit the growth of the two fungi. The measurement of optical properties showed that the transparency of the edible film was highest at the addition of 0% olive oil at 55%. The highest opacity value was with the addition of 1% olive oil, which is 2.96. The Fourier Transform Infrared (FTIR) identification showed that the edible film added with 1% olive oil had three characteristic absorption bands from gluten, olive oil, and an absorption band from glycerin. These bands indicate that olive oil, glycerin, and gluten do not react but only physically interact. The measurement using Scanning Electron Microscopy (SEM) and Energy Dispersive Spectrometer (EDS) showed that the microstructure of gluten-based edible film produces a varied structure where the gluten structure network can be clearly observed and contains elements of C, O, N where the intensity of C and O elements of 160-400 cps and 30-100 cps, respectively.